Determinants of Anemia Occurance In Adolescent Girls - Amaliah, Cindy Klaodia; Fitriyani (Jurnal Kebidanan Midwiferia, 2026)
Anemia among adolescent girls is a global health problem affecting physical health, academic performance, and well-being. Increased iron requirements during adolescence are often unmet due to poor dietary intake, irregular menstruation, low adherence to iron supplementation, limited physical activity, and unfavorable socioeconomic conditions. This study aimed to analyze the association between these factors and anemia among adolescent girls in Pekalongan Regency and to identify the most influential factor. A quantitative cross-sectional study was conducted with 190 respondents selected through cluster random sampling. Data were collected using questionnaires and digital hemoglobin measurements and analyzed using univariate, Chi-square, and multiple logistic regression tests. Most respondents had poor dietary intake (77.9%), irregular menstruation (68.9%), low adherence to iron tablets (60.5%), insufficient physical activity (74.7%), and low socioeconomic status (52.1%). More than half (54.2%) were anemic. Bivariate tests found that all variables were significantly related to the prevalence of anemia (p<0.05). With a 95% CI The results showed dietary pattern (OR=19.194), menstrual pattern (OR=8.910), Fe tablet consumption (OR=4.517), physical activity (OR=3.585), and economic status (OR=5.161). Multivariate analysis identified dietary pattern as the most dominant factor associated with anemia (OR=19.194; p<0.001). Dietary habits are the strongest determinant of anemia among adolescent girls. Prevention efforts should prioritize balanced nutrition, reproductive health education, improved adherence to iron supplementation, regular physical activity, and awareness of affordable nutritious foods.